2014
DOI: 10.1590/s1517-83822014000400012
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of silver nanoparticles synthesized by marine Ochrobactrum sp.

Abstract: Metal nanoparticle synthesis is an interesting area in nanotechnology due to their remarkable optical, magnetic, electrical, catalytic and biomedical properties, but there needs to develop clean, non-toxic and environmental friendly methods for the synthesis and assembly of nanoparticles. Biological agents in the form of microbes have emerged up as efficient candidates for nanoparticle synthesis due to their extreme versatility to synthesize diverse nanoparticles with varying size and shape. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(29 citation statements)
references
References 35 publications
1
26
0
1
Order By: Relevance
“…These results agreed with previous work carried out by Hungund et al [38], Thomas et al [39], and Chitra and Annadurai [40].…”
Section: Antimicrobial Assaysupporting
confidence: 94%
“…These results agreed with previous work carried out by Hungund et al [38], Thomas et al [39], and Chitra and Annadurai [40].…”
Section: Antimicrobial Assaysupporting
confidence: 94%
“…The poor antibacterial activity is due to the larger particle size of AgNPs [9]. When the particle size of AgNPs is around 10-50 nm, the MIC and MBC are approximately 10 times less than this study results [6][7][8].…”
Section: Minimum Inhibitory Concentration/minimum Bactericidal Concenmentioning
confidence: 59%
“…Green synthesis of silver nanoparticles (AgNPs) by using different parts of plant such as leaf [4], stem [5], and root [6], microorganism [7,8], and biopolymers such as starch [9], chitosan [10], lignin [11], latex [12] as a reducing agent, have been reported previously. Besides, studies reported limited synthesis of AgNPs using agricultural waste such as Annono squamosa and mango peel extracts [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we have already reported the AgNP-synthesizing properties of a wide range of bacteria [25][26][27]. Among these, Bacillus amyloliquefaciens was found to have an ability to form highly stable AgNPs.…”
Section: Resultsmentioning
confidence: 99%